Death and Dying in Colonial Spanish America - Will de Chaparro, Martina; Achim, Miruna (University of Arizona Press, 2011)
When the Spanish colonized the Americas, they brought many cultural beliefs and practices with them, not the least of which involved death and dying. The essays in this volume explore the resulting intersections of cultures through recent scholarship related to death and dying in colonial Spanish America between the sixteenth and eighteenth centuries. The authors address such important questions as: What were the relationships between the worlds of the living and the dead? How were these relationships sustained not just through religious dogma and rituals but also through everyday practices? How was unnatural death defined within different population strata? How did demo-graphic and cultural changes affect mourning?The variety of sources uncovered in the authors' original archival research suggests the wide diversity of topics and approaches they employ: Nahua annals, Spanish chronicles, Inquisition case records, documents on land disputes, sermons, images, and death registers. Geographically, the range of research focuses on the viceroyalties of New Spain, Peru, and New Granada.The resulting records-both documentary and archaeological-offer us a variety of vantage points from which to view each of these cultural groups as they came into contact with others. Much less tied to modern national boundaries or old imperial ones, the many facets of the new historical research exploring the topic of death demonstrate that no attitudes or practices can be considered either "Western" or universal.